Plasma methylcitric acid and its correlations with other disease biomarkers: The impact in the follow up of patients with propionic and methylmalonic acidemia. Issue 6 (23rd August 2020) - Maines, Evelina; Catesini, Giulio; Boenzi, Sara; Mosca, Antonella; Candusso, Manila; Dello Strologo, Luca; Martinelli, Diego; Maiorana, Arianna; Liguori, Alessandra; Olivieri, Giorgia; Taurisano, Roberta; Piemonte, Fiorella; et al.
Abstract: Methylcitric acid (MCA) analysis has been mainly utilized for the diagnosis of propionate disorders or as a second‐tier test in newborn screening, but its utility for patients monitoring still needs to be established. We explored the potential contribution of MCA in the long‐term management of organic acidurias. We prospectively evaluated plasma MCA and its relationship with disease biomarkers, clinical status, and disease burden in 22 patients, 13 with propionic acidemia (PA) and nine with methylmalonic acidemia (MMA) on standard treatment and/or after transplantation. Samples were collected at scheduled routine controls or during episodes of metabolic decompensation (MD), 10 patients were evaluated after transplantation (six liver, two combined liver and kidney, 2 kidney). MCA levels were higher in PA compared to MMA and its levels were not influenced by the clinical status (MD vs well state). In MMA, MCA was higher in elder patients and, along with fibroblast growth factor 21 (FGF21) and plasma methylmalonic acid, negatively correlated with GFR. In both diseases, MCA correlated with ammonia, glycine, lysine, C3, and the C3/C2, C3/C16 ratios. The disease burden showed a direct correlation with MCA and FGF21, for both diseases. All transplanted patients showed a significant reduction of MCA in comparison to baseline values, with some differences dependent on the type of transplantation. Our study provided new insights in understanding the disease pathophysiology, showing similarities between MCA and FGF21 in predicting disease burden, long‐term complications and in evaluating the impact of organ transplantation.